2010
DOI: 10.1007/s00249-010-0649-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of topographic microstructures on the initial adhesion of L929 fibroblasts studied by single-cell force spectroscopy

Abstract: Single-cell force spectroscopy was used to investigate the initial adhesion of L929 fibroblasts onto periodically grooved titanium microstructures (height ~6 μm, groove width 20 μm). The position-dependent local adhesion strength of the cells was correlated with their rheological behavior. Spherical cells exhibited a significantly lower Young’s modulus (<1 kPa) than that reported for spread cells, and their elastic properties can roughly be explained by the Hertz model for an elastic sphere. While in contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…In addition, our findings on CS (0.17-2.08 nN/lm) are in corroboration with their data ($0.2 -$1.8 nN/lm). In another study concerning the adhesion of murine L929 fibroblasts to microstructured titanium, 26 detachment forces of the same force range ($3 nN) were revealed after 1 min of interaction between cells and surfaces. Even though the cell line, the interaction time, and sample preparation differed in our study, these comparisons show that the range of detachment forces after less than 1 min of cell-substrate-interaction should lie in an interval between some hundred of piconewtons and a few nanonewtons.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition, our findings on CS (0.17-2.08 nN/lm) are in corroboration with their data ($0.2 -$1.8 nN/lm). In another study concerning the adhesion of murine L929 fibroblasts to microstructured titanium, 26 detachment forces of the same force range ($3 nN) were revealed after 1 min of interaction between cells and surfaces. Even though the cell line, the interaction time, and sample preparation differed in our study, these comparisons show that the range of detachment forces after less than 1 min of cell-substrate-interaction should lie in an interval between some hundred of piconewtons and a few nanonewtons.…”
Section: Discussionmentioning
confidence: 80%
“…Chemical and physical surface properties such as texture, roughness, and porosity determine the extent of FBR 18–22. It has been shown that cells strongly respond to nano‐ and microstructures 23–30. However, the underlying mechanisms are not fully understood 31.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion phenomenon, characterized as negative force in the experimental force-displacement curves obtained in AFM nanoindentation, was widely reported over the last two decades [10][11][12][13]. The adhesion behavior of cells with other nanoparticles is crucial for the biocompatibility of implants [14]. In recent years, it becomes clear that adhesion molecules are involved in tethering cells to specific locations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interactions between the cells and the extracellular matrix (ECM) contribute in the maintenance of the structural integrity of tissues 21 . In addition, the adhesive behaviour of cell with other surfaces is crucial for the biocompatibility of implants 7 . Cell adhesion is a dynamic process, which is controlled by the binding of adhesion molecules on the cell surface 23 .…”
Section: Introductionmentioning
confidence: 99%